Critical heat flux enhancement of HFE-7100 flow boiling in a minichannel heat sink with saw-tooth structures. (February 2017) - Fu, Ben-Ran; Chung, Shan-Yu; Lin, Wei-Jen; Wang, Lei; Pan, Chin
A heat sink with convective boiling in micro- or mini-channels is with great potential to meet the requirement of the high heat dissipation of the electronic devices. This study investigates the flow boiling of HFE-7100, having a suitable boiling temperature at atmospheric pressure and dielectric property, in the minichannel heat sink with the modified surface (namely, the saw-tooth structure). The effect of the system pressure on the boiling characteristics was also studied. The results reveal that the critical heat flux can be significantly improved by introducing the saw-tooth structures on the channel surface or boosting the system pressure as well as by increasing the mass flux. Compared to the non-modified channel, the enhancements of the critical heat flux for the parallel and counter saw-tooth channels are 44% and 36%, respectively, at the small mass flux. The boiling visualization further indicates that the minichannels with the saw-tooth structures interrupt the boundary layer and restrain the coalescence of the bubble, which may be the reason for the critical heat flux enhancement. Moreover, the degree of the critical heat flux enhancement, contributed by the saw-tooth modification of the channel, decreases with an increase in the mass flux.